Evaluation of Factors Influencing Outcome of Extracorporeal Shock Wave Lithotripsy (Eswl) for Renal Stone in Adult (Bangladesh Journal of Urology, 2020)
Background: Renal stone disease is a common disorder with a prevalence ranging from 4-15% in different parts of the world. Modalities of kidney stone management includes drug therapy, extracorporeal shock wave lithotripsy (ESWL), percutaneous nephrolithotomy (PCNL), Retrograde intrarenal surgery ureteroscopy (RIRS) and open surgery. ESWL is an acceptable technique and widely used because it is a non-invasive treatment and does not require anesthesia and usually done on an outpatient basis. Generally, ESWL is the treatment of choice for kidney stones